2020
DOI: 10.3390/jcm9082652
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of a Myofunctional Appliance on Atypical Swallowing and Lip Strength: A Prospective Study

Abstract: Atypical swallowing needs treatment in order to eliminate harmful interferences of the tongue, which prevent the harmonious growth of the stomatognathic system. The purpose of this study was to assess the effects of a functional appliance on the presence of atypical swallowing, analyzing the lip strength and the altered facial mimics. The effects of a myofunctional appliance (the Froggy Mouth) were evaluated on 40 children (6 males; 24 females; mean age 9.6 ± 2.17) with atypical swallowing—with tongue thrust d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
1
8
0
3
Order By: Relevance
“…Kaede et al demonstrated that lip‐closing training enhances LCS in healthy younger adults (Kaede et al, 2016). Quinzi et al reported increased lip strength and achieved clinical correction of atypical swallowing (Quinzi et al, 2020). Furthermore, Ingervall and Carlsson reported that lip‐closing training influences lip soft tissue formation in children with ILS, which increases the height of both lips and decreases the interlabial gap (Ingervall & Carlsson, 1982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaede et al demonstrated that lip‐closing training enhances LCS in healthy younger adults (Kaede et al, 2016). Quinzi et al reported increased lip strength and achieved clinical correction of atypical swallowing (Quinzi et al, 2020). Furthermore, Ingervall and Carlsson reported that lip‐closing training influences lip soft tissue formation in children with ILS, which increases the height of both lips and decreases the interlabial gap (Ingervall & Carlsson, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of myofunctional treatment during growing periods was limited to several reports of children with neuromuscular dysfunction, such as a lip training method for patients with intellectual disability or lip deformation (da Costa et al, 2018; Pinheiro et al, 2018; Saccomanno et al, 2018). To date, limited studies have analyzed the effects of oral functional training during developmental periods (Quinzi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…En ocasiones, la maduración fisiológica del mecanismo de deglución no se ha desarrollado por completo; un patrón infantil, llamado "deglución atípica", persiste más allá del límite fisiológico. En consecuencia, durante la deglución, se produce un empuje de la lengua hacia adelante, generalmente a nivel de las superficies palatinas de los incisivos superiores, o la lengua se interpone entre las arcadas dentarias, acompañada de una contracción de los músculos mímicos, en particular de los músculos orbicular de los labios y borla del mentón 16 .…”
Section: Deglución Atípicaunclassified
“…ED produce light and biological elastic forces to correct malocclusions, changing the position of the teeth and potentially affecting growth of the bone bases, by stimulating the perioral muscles [ 5 ] and remodeling and relocation of the glenoid fossa. These appliances are used with children with primary dentition as, when muscular interferences or dento-skeletal malocclusions are treated at a very early stage, it seems to improve the stability of relationship between the jaws, and their muscular component [ 6 , 7 ]. Their main clinical applications described in the literature are for increased overjet and overbite, gummy smile, anterior crowding and rotations, open bite, class II malocclusion, and scissor bite [ 8 ].…”
Section: Introductionmentioning
confidence: 99%